Numerous speeds-loads controller for DC-shunt motor based on PID controller with on-line parameters tuning supported by genetic algorithm - Mazin Abdulelah Alawan; Oday Jasim Mohammed Al-Furaiji (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Direct-current (DC) motor is a commonly used motor; its speed is directly affected by applying mechanical load. This paper proposes the design of wide speed-load range controller for a direct-current (DC) shunt motor based on proportional–integral–derivative (PID controller) with genetic system for controller parameters adjusting. The genetic based PID controller is simulated by using Matlab software package and tested with different sudden load values and different working speeds. A present control loop contains the suggested PID controller also Pulse-Width-Modulation PWM generator and H-bridge inverter. With the genetic system enhancement to parameters of developed PID controller, the results demonstration that this controller has great impact to preserve the profiles of the motor speed and produced torque after applied sudden load, and its intensification the motor performance at different speed and load conditions.